Islam Indonesia Pluralitas Aliran Dan Paradigma Normatif-Historis - Alfanny, M. Sa'ad; Sirojuddin, Ahmad Sholihin; Kamal Yusuf; Nur Tamimah; Ach Badri Amien (AL-Ikhtiar : Jurnal Studi Islam, 2025)
Indonesia as a country with religious and cultural plurality presents complex dynamics in the development of Islamic sects. This diversity poses challenges in understanding the changes and sustainability of religious sects holistically. This article examines the normative-historical paradigm as a new approach that integrates the dimensions of religious norms and historical context in the study of Indonesian Islamic sects. The research method used is a literature review with a comparative approach that analyses Islamic literature, historical documents, and the results of previous research on traditionalist, modernist, and contemporary sects. The results of the discussion show that the normative-historical paradigm is able to bridge the tension between normative religious teachings and dynamic socio-historical reality, thus providing a richer understanding of the process of transformation and sustainability of Islamic sects. This paradigm not only helps identify internal and external factors that influence sect change, but also emphasises the importance of accommodating plurality within an inclusive religious framework. Thus, the normative-historical paradigm offers a significant contribution in strengthening the study of Indonesian Islam in an increasingly complex and diverse contemporary era. Abstrak Indonesia sebagai negara dengan pluralitas agama dan budaya menghadirkan dinamika kompleks dalam perkembangan aliran-aliran Islam. Keberagaman ini menimbulkan tantangan dalam memahami perubahan dan keberlanjutan aliran keagamaan secara holistik. Artikel ini mengkaji paradigma normatif-historis sebagai pendekatan baru yang mengintegrasikan dimensi norma keagamaan dan konteks historis dalam studi aliran Islam Indonesia. Metode penelitian yang digunakan adalah kajian pustaka dengan pendekatan komparatif yang menganalisis literatur keislaman, dokumen sejarah, dan hasil penelitian terdahulu tentang aliran tradisionalis, modernis, dan kontemporer. Hasil pembahasan menunjukkan bahwa paradigma normatif-historis mampu menjembatani ketegangan antara ajaran agama yang bersifat normatif dengan realitas sosial-historis yang dinamis, sehingga memberikan pemahaman yang lebih kaya tentang proses transformasi dan keberlanjutan aliran-aliran Islam. Paradigma ini tidak hanya membantu mengidentifikasi faktor internal dan eksternal yang mempengaruhi perubahan aliran, tetapi juga menegaskan pentingnya mengakomodasi pluralitas dalam kerangka keagamaan yang inklusif. Dengan demikian, paradigma normatif-historis menawarkan kontribusi signifikan dalam memperkuat kajian Islam Indonesia di era kontemporer yang semakin kompleks dan beragam.